Linguistic syntagmatics in the verbal conflict - Onuchak, Liudmyla Volodymyrivna; Chaika, Larysa Vasylivna (Ca’Foscari University of Venice, 2020)
The concept of verbal conflict is such a violation of the human communication process, when one of the communicants does not fully or partially understand the other, has a negative attitude to his/her manner of speech behavior, verbal-cognitive base or to the signs used in the communicative act. The verbal conflict concept provides an opportunity to generalize and theoretically comprehend the whole complex of similar phenomena of speech interaction, which were previously either studied sporadically or not included in a number of linguistic objects at all.

Поняття словесного конфлікту є таким порушенням процесу людського спілкування, коли один з комунікантів не повністю або частково розуміє іншого, негативно ставиться до своєї мовної поведінки, словесно-пізнавальна база або знаки, що використовуються в комунікативній акті. словесне поняття конфлікту дає можливість узагальнити і теоретично осмислити весь комплекс подібних явищ мовної взаємодії, які раніше або вивчалися епізодично, або взагалі не включалися в ряд мовних об'єктів.
Keywords: verbal conflict; linguistic syntagmatics; human communication process; словесний конфлікт; лінгвістична синтагматика; процес людського спілкування